2015
DOI: 10.1186/s12960-015-0055-x
|View full text |Cite
|
Sign up to set email alerts
|

A path analysis study of retention of healthcare professionals in urban India using health information technology

Abstract: BackgroundHealthcare information technology (HIT) applications are being ubiquitously adopted globally and have been indicated to have effects on certain dimensions of recruitment and retention of healthcare professionals. Retention of healthcare professionals is affected by their job satisfaction (JS), commitment to the organization and intention to stay (ITS) that are interlinked with each other and influenced by many factors related to job, personal, organization, etc. The objectives of the current study we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 60 publications
2
42
0
Order By: Relevance
“…From Table 1, it can be inferred that test results with SEM review conducted using the AMOS version of the program information technology 21 shows that notable positive impact on job satisfaction. This analysis indicates the findings were consistent with what is expressed Bhattacharya and Ramachandran (2015) IT was highlighted as one of the factors that could affect job satisfaction. Likewise raised by Chiu et.al (2007) that notes that the quality program affects user's satisfaction, the quality of information, and the use of the system.…”
Section: B the Influence Of Information Technology On Job Satisfactionsupporting
confidence: 85%
“…From Table 1, it can be inferred that test results with SEM review conducted using the AMOS version of the program information technology 21 shows that notable positive impact on job satisfaction. This analysis indicates the findings were consistent with what is expressed Bhattacharya and Ramachandran (2015) IT was highlighted as one of the factors that could affect job satisfaction. Likewise raised by Chiu et.al (2007) that notes that the quality program affects user's satisfaction, the quality of information, and the use of the system.…”
Section: B the Influence Of Information Technology On Job Satisfactionsupporting
confidence: 85%
“…The results of the analysis revealed that the CHCs with a low number of health workers (fewer than 10) are expected to have a low number of specialists. It is possible that those CHCs with a low number of health workers face a higher burden of work that forces specialists to move out to health facilities staffed with higher numbers of health workers, thus experiencing relatively lower burden [59, 60]. The results of the regression analysis also revealed that those CHCs that had residences available for specialists are expected to have a higher number of specialists than those CHCs that do not have residences for specialists.…”
Section: Discussionmentioning
confidence: 99%
“…Available studies on ICT in health in rural and remote areas have emphasised mainly the benefits of ICT in work processes with little attention to the contributions that ICT might make on the retention of health workers. Bahttacharya and Ramachandran [13] have suggested that ICT is among the factors that can reasonably influence health workers’ intention to stay in urban health facilities in India. Further, training and explaining the benefits of ICT to health workers may also improve retention.…”
Section: Introductionmentioning
confidence: 99%